Em defesa da beleza: o sagrado e a filosofia da beleza de Roger Scruton - Arielo, Flávia Santos (2019)
This thesis aims to reveal the vision of beauty and the sacred from the contemporary British philosopher Sir Roger Scruton, whose intellectual output extends to the aesthetics, political philosophy and philosophy of religion. Having as its starting point his work named Beauty, the author places himself as a defender of the concept of beauty in what concerns, mainly, the plastic arts, music and architecture. The goal of this research is to analyze Scruton's understanding of beauty and how it relates it to the question of the sacred. For that, it is necessary to deepen in the conservative thought of which Roger Scruton participates and defends, evidencing the authors who based their aesthetic and philosophical arguments. The main hypothesis’s based on the defense of the beauty of Scruton as a way of salvation of the world, since, from the modern art, the beauty was separated from the artistic production and desecrated by means of what the author defines as kitsch. From the bibliographical survey of his works, as well as his critical fortune, this research revealed that Roger Scruton produces a philosophy of beauty, which aims, mainly, to preserve and disseminate it in the contemporary world, taking as essential and irreplaceable aspects sacred and religious